2020
DOI: 10.1002/cssc.202000440
|View full text |Cite
|
Sign up to set email alerts
|

Polydiacetylene–Perylenediimide Supercapacitors

Abstract: Organic supercapacitors have attracted interest as promising “green” and efficient components in energy storage applications. A polydiacetylene derivative coupled with reduced graphene oxide was employed, for the first time, to generate an organic pseudocapacitance‐based supercapacitor that exhibited excellent electrochemical properties. Specifically, diacetylene monomers were functionalized with perylenediimide (PDI), spontaneously forming elongated microfibers. Following polymerization through UV irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…This conclusion can also be confirmed by the Nyquist plots of the electrodes, as shown in Figure 4E . Both the Nyquist plots of the two electrodes contain one semicircle in high frequency region corresponding to charge transform resistance at electrolyte/electrode interface and an upward line in low frequency region associated with ion diffusion in electrolyte ( Adhikari et al, 2020 ; Gurten and Aktas, 2020 ; Pang and Wang, 2021 ). The Ni-AC electrode has smaller charge transferring resistance than that of the AC, which contributes to the enhanced graphitization degree boosting conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion can also be confirmed by the Nyquist plots of the electrodes, as shown in Figure 4E . Both the Nyquist plots of the two electrodes contain one semicircle in high frequency region corresponding to charge transform resistance at electrolyte/electrode interface and an upward line in low frequency region associated with ion diffusion in electrolyte ( Adhikari et al, 2020 ; Gurten and Aktas, 2020 ; Pang and Wang, 2021 ). The Ni-AC electrode has smaller charge transferring resistance than that of the AC, which contributes to the enhanced graphitization degree boosting conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Supercapacitors, as a kind of promising energy storage device with high power density and long service life, have excited great interest owing to their potential application in portable electronics and electric vehicles ( Qin et al, 2021 ; Reece et al, 2020 ; Yang L et al, 2021 ; Zhu et al, 2019 ). Based on different energy storage mechanisms, supercapacitors are mainly divided into two categories: faradic pseudocapacitors, in which transition metal oxides and conducting polymers are used as active materials, and electrical double-layer capacitors (EDLCs), in which carbon-based materials are often used as active materials ( Adhikari et al, 2020 ; Liu T et al, 2020 ; Say et al, 2020 ). The energy storage mechanism of EDLCs depends on the attraction of positive and negative charges at the interface of electrode and electrolyte, enabling high power density and ultralong cycling life of EDLCs ( Fleischmann et al, 2020 ; Pai et al, 2021 ; Pourhosseini et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a porous PDI–polydopamine–rGO electrode specific capacitance of 610 F g −1 was generated via ultraviolet irradiation. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a porous PDI-polydopamine-rGO electrode specific capacitance of 610 F g −1 was generated via ultraviolet irradiation. [18] In this study, we successfully designed and synthesized a new type of quinone-like organic molecule (naphthalene diimide (NDI)), with a large symmetrical conjugate structure and two electron-withdrawing imide groups. The NDI molecule was used as a guest to modify rGO sheets to obtain the rGO-NDI composition by using non-covalent strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Moreover, the literature search revealed that PDI derivatives are utilized to fabricate efficient SC electrode materials. [36][37][38][39] Recently, pyridine-based covalent organic framework (COF)-based organic materials are utilized for SC applications. [40] Though pyridine-based COF showed significant SC properties, its direct use in small molecule-based SC electrode has limited precedent.…”
mentioning
confidence: 99%